Model pembelajaran fisik berbasis permainan untuk meningkatkan keterampilan motorik kasar pada siswa usia dini - Purwanto, Didik; Rejeki, Hendriana Sri; Mentara, Hendrik (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
Limited diversity in learning approaches frequently results in suboptimal gross motor development among younger students. A play-based approach enhances motor development in a manner that is both more engaging and effective. Exploring a robust game-oriented pedagogical framework aimed at improving the gross motor abilities of elementary students. Utilizing game-based approaches in physical education enhances the engagement and efficacy of the learning experience, particularly in fostering motor development. This study employed a classroom action research methodology, focusing on students from elementary school Unggulan Putra Kaili Permata Bangsa in Palu City. The research utilized total sampling, encompassing a cohort of 25 students from the lower grades. This research instrument employs a performance rubric to analyze gross motor assessment in lower-grade children, a methodology that has been substantiated by experts in their respective fields. Analysis of data using the traditional completeness formula. The findings indicated that the initial percentage prior to the cycle stood at 4%; during cycle I, it escalated to 24%, and in cycle II, it reached an impressive 96%. The results indicated a progressive increase in each cycle, specifically demonstrating an improvement of 92% from the initial cycle to cycle II. The overall proficiency in gross motor skills among the students of Elementary school Unggulan Putra Kaili Permata Bangsa in Palu City is noteworthy. This research presents a novel, more comprehensive, contextualized, and purposeful approach to play-based physical learning aimed at tackling the challenges encountered by low-grade students in their gross motor development.